Brain Interleukin-1 Facilitates Learning of a Water Maze Spatial Memory Task in Young Mice - Takemiya, Takako; Fumizawa, Kumiko; Yamagata, Kanato; Iwakura, Yoichiro; Kawakami, Marumi (Frontiers in Behavioral Neuroscience, 2017)
The proinflammatory cytokine interleukin-1 (IL-1) is produced by many types of cells, including immune cells in the periphery and glia and neurons in the brain. The type I IL-1 receptor (IL-1r1) is primarily responsible for transmitting the inflammatory effects of IL-1 and mediates several biological functions by binding to either IL-1α or IL-1β. IL-1β activation is associated with hippocampus-dependent memory tasks. Although IL-1β impairs spatial memory under certain pathophysiological conditions, IL-1β may be required for the normal physiological regulation of hippocampal plasticity and memory. In addition, brain IL-1β levels are thought to change in the hippocampus in an age-dependent manner. These findings suggest that IL-1β may have a beneficial, temporary effect on learning and memory in young mice, but the matter remains unclear. Therefore, we hypothesized that hippocampal IL-1β has a beneficial effect on spatial learning and memory in young mice via IL-1r1, which is diminished in adults. We investigated the performance of young (3-month-old) and adult (6-month-old) wild-type mice (wt), IL-1β knockout mice (IL-1βko) and IL-1r1 knockout mice (IL-1r1ko) in learning a spatial memory task with a fixed platform (PF) in a water maze (WM) and measured the levels of IL-1β and IL-1α in the hippocampus and cortex of adult and young mice by using homogeneous time-resolved fluorescence (HTRF). Learning was significantly impaired in the training trials of the WM spatial memory task in young IL-1βko and IL-1r1ko mice but not in adult IL-1βko and IL-1r1ko mice. Moreover, young IL-1r1ko mice but not IL-1βko mice showed an impairment in long-term memory extinction, suggesting that IL-1α might facilitate memory extinction. In this study, the cytokine assay using HTRF did not indicate a higher expression of hippocampal IL-1 in young mice but cortical IL-1β and IL-1α were significantly increased in adult mice. We need to investigate the role of cortical IL-1 and the local IL-1 expression in the hippocampal neurons in the future.